Розробка каталізатора синтезу компонентів моторного палива з вуглецьвмісної сировини - Trypolsky, Andriy І.; Fatieiev, Danylo S.; Pyanykh, Kostyantyn Ye.; Ivanenko, Olena I.; Bychko, Ihor B.; Stolyarchuk, Irina L.; Strizhak, Peter Ye. (Каталіз та нафтохімія, 2025)
The article is devoted to the development of an iron-containing catalyst for the synthesis of liquid hydrocarbons over modular units (Fischer-Tropsch process) from synthesis gas obtained by gasification of carbon-containing feedstock. Based on literature data, nine laboratory catalyst samples were synthesized; they differed in both qualitative and quantitative chemical composition as well as in the preparation method. Experimental investigation of the catalytic properties of the synthesized iron-containing catalysts in the Fischer–Tropsch reaction made it possible to select the catalytic composite C3, which served as the basis for designing an original technology for industrial production of an efficient catalyst for the synthesis of liquid hydrocarbons from carbon-containing feedstock, and for producing a pilot batch. The developed industrial catalyst had the following composition: 67.6 % Fe2O3, 20.0 % CuO, 2.5 % K2O, 9.9 % Al2O3; the specific surface area of the non-activated catalyst was 24.42 m²/g. This catalyst was characterized using various physicochemical methods, and its catalytic performance was studied in a laboratory unit using a model synthesis-gas mixture. It was shown that, during the Fischer–Tropsch synthesis in the presence of the developed catalyst, iron carbides FexC are formed, with their content ranging from 2.0 to 31 % of the total amount of components. Optimal process conditions were determined, and liquid hydrocarbons were synthesized from synthesis gas using the developed catalyst. It was demonstrated that, under standard conditions (CO:H₂ = 1:3, gas hourly space velocity 2400 h⁻¹, pressure 5 atm, temperature 280 °C), the CO conversion reached 49.8 %, while the yield of liquid hydrocarbons was 0.153 g/(gcat·h), corresponding to a selectivity of 42 % toward liquid hydrocarbons. Successful tests of the developed catalyst were carried out in a pilot unit using synthesis gas produced by wood gasification.